PROBLEMATIKA PEMBAGIAN HARTA WARISAN PASCA TSUNAMI DI KABUPATEN ACEH BARAT (Studi Kasus Kecamatan Johan Pahlawan Kabupaten Aceh Barat) - Fariani Fariani (Islam Futura, 2014)
Inheritance law occupies an important role in Islamic law. In West Aceh, at every distribution of inheritance raises some issues which ultimately bring about to the death. The problem what is the inheritance distribution problem after tsunami at Johan Pahlawan sub-district in West Aceh, what is the solution on the problematic inheritance distribution at Johan Pahlawan sub-district of West Aceh. Method of the research is qualitative research. This research is field research. Therefore, the researcher conducted observations, interviews and documents analysis to know the problem related to the problem of the study. It shows that the distribution of the inheritance problem after tsunami that lack of expert in faraidh, the loosing of lands’ documents ownership, the loosing of inheritance objects and haste distribution. The majority of the society at Johan Pahlawan sub-district of West Aceh is Muslim as there is influences of Islamic culture then the inheritance distribution are: the total inheritance of parents, but in the community itself is also common division based on an agreement with the family usually initiate of the male heirs.